2022
DOI: 10.1186/s12974-022-02613-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in microglia: a novel perspective for pathogenesis of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease in the elderly globally. Emerging evidence has demonstrated microglia-driven neuroinflammation as a key contributor to the onset and progression of AD, however, the mechanisms that mediate neuroinflammation remain largely unknown. Recent studies have suggested mitochondrial dysfunction including mitochondrial DNA (mtDNA) damage, metabolic defects, and quality control (QC) disorders precedes microglial activation and subsequent neuroinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 136 publications
0
28
0
Order By: Relevance
“…Microglia, which are innate immune cells of CNS, play a vital role in clearing pathogenic molecules and mediating the neuroinflammatory reaction [ 26 , 66 ]. Under pathological conditions, PAMP or DAMP induces the activation of microglia and NLRP3 inflammasome and resulting in neuroinflammation [ 34 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia, which are innate immune cells of CNS, play a vital role in clearing pathogenic molecules and mediating the neuroinflammatory reaction [ 26 , 66 ]. Under pathological conditions, PAMP or DAMP induces the activation of microglia and NLRP3 inflammasome and resulting in neuroinflammation [ 34 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microglial activation-induced neuroinflammation is one of the important mechanisms underlying the pathogenesis of AD [ 26 , 70 , 71 ]. Several lines of evidence suggest that mitochondrial malfunction of microglia induces microglial activation and is involved in AD pathogenesis [ 66 ]. The accumulation of Aβ within mitochondria causes mitochondrial dysfunction and oxidative stress [ 70 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the most deregulated metabolites in the cortex of Pde2a +/− mice (glutathione and purine metabolism) are well known to contribute to oxidative stress (62). Recent studies have suggested that mitochondrial dysfunction, including mitochondrial DNA (mtDNA) damage, metabolic defects, and quality control disorders, precedes microglial activation and subsequent neuroinflammation (63). In this context, mitochondrial alterations may be associated with microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory microglia can significantly alter energy metabolism in the brain, leading to impaired neuronal network function and blood-brain barrier dysfunction [70]. Pathophysiology in which changes in specific proteins lead to dysfunction in a number of different cellular pathways, including mitochondrial dysfunction, excitotoxicity, synaptic dysfunction, damage to protein degradation systems, ER stress, DNA damage, inflammation, and increased levels of reactive oxygen species (ROS) due to cell cycle re-entry [71], which in turn lead to the production of AD.…”
Section: 11admentioning
confidence: 99%